Factors Predicting Health Promoting Behaviors of the 3rd Year Students, University of Phayao, During COVID-19 Situation - Chaiyot, Pinyada; Sirinual, Sutichai; Lamluk, Prachuab; Jadsri, Somchai; Manoton, Anukool (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2023)
This cross-sectional descriptive study aimed to examine health promotion behaviors and identify factors predicting those behaviors during the COVID-19 situation among third-year students at the University of Phayao. A total of 273 participants, who were health science students, were selected using multistage random sampling. Data were collected through self-administered questionnaires and analyzed using frequency, percentage, mean, standard deviation, and Pearson Product Moment Correlation. The findings indicated that health-promoting behaviors were at a moderate level (72.90%) when considering various aspects, such as leading factors, contributing factors, and supporting factors. Additionally, knowledge about health-promoting behaviors, attitudes, perceptions of the benefits of health promotion, supporting activities and policies related to health promotion, and high levels of access to health support information were observed. The perceived obstacles to health promotion were moderate, and several factors were identified as predictors of health promotion behaviors among third-year students during the COVID-19 epidemic. The overall result showed a 46.40 percentage association (R2 = 0.46, p-value < 0.05) with supporting information, health knowledge, perceived benefits of health promotion, body mass index (BMI), and attitude towards health promotion.